Structural Imbalances in Canadian Labor Markets - Gera, S.; Rahman, S. S.; Arcand, J. L. (Journal of Income Distribution®, 1994)
The nature of structural imbalances in the Canadian Labor market is identified by analyzing the relationship between unemployment and job vacancies. Three potential sources of imbalances are examined: (1) the regional nature of the Canadian economy; (2) the rise in the incidence of long-term unemployment (of 12 months or more); and (3) differences in the rate of growth of unemployment across industrial sectors. The major findings are: growing structural imbalances; an increase in long-term unemployment was the major cause of the shift in most cases; both inter-and intraregional effects played a significant role, but interregional disparities were the dominant factor; and the dispersion in employment growth rates across industrial sectors did not seem to play a role.